A Predictive Model for the Strength of a Novel Geopolymer Construction Material Produced by Autoclaved Aerated Concrete Waste - Mollaei, Somayeh; Fahmi, Ahmad; Jahani, Davoud; Babaei Golsefidi, Zohre; Babaei, Reza; Hanafi, Mohammad Reza (International Journal of Sustainable Construction Engineering and Technology, 2023)
Carbon dioxide emission and consumption of large amounts of natural resources are the environmental hazards observed in the production process of various commonly used construction materials, like Portland cement and clay bricks. Also, debris from the demolition of old buildings and disposing of the waste of construction material factories also cause environmental pollution. Producing environmentally friendly geopolymer materials with recycling construction wastes containing aluminosilicate resources and alkaline activators could be an effective method for reduction of environmental hazards. This paper is an innovative feasibility study of geopolymer material production using the waste autoclaved aerated concrete (AAC) powder. Here, a mix of AAC powder together with activator solution containing sodium hydroxide and sodium silicate at different concentrations was used to prepare the geopolymer mortar samples. The specimens were oven-cured at different temperatures. The effects of sodium hydroxide concentration and curing temperature on the compressive, tensile, and flexural strengths, as well as water absorption of the samples, were investigated. The main contribution of this study is the feasibility of the successful fabrication of geopolymer material based on AAC waste powder with desirable mechanical properties. Namely, the compressive strength of the base AAC blocks used here was 3 MPa and the maximum strength of the produced geopolymer material using the AAC powder was about 21 MPa. The test results were used to develop a model to predict the compressive strength of the proposed geopolymer AAC material to the effective parameters by Gene Expression Programming. The model predictions were confirmed using an extra series of test results implemented by the authors.